2015
DOI: 10.9778/cmajo.20140130
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus nonoperative interventions for common fractures of the clavicle: a meta-analysis of randomized controlled trials

Abstract: C lavicle fractures are common injuries, affecting about 22 000 Canadians each year and numbering 1.75 million fractures worldwide. [1][2][3][4][5][6] The majority of these fractures are located in the midshaft, accounting for about 80% of all clavicle fractures.1,2 Closed midshaft fractures were traditionally treated nonoperatively, a practice largely based on previous studies by Neer and Rowe. 7,8 In the last decade, evidence challenged the standard of nonoperative treatment, reporting high rates of nonunio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(84 reference statements)
0
10
1
Order By: Relevance
“…Compared to the study by Woltz et al, [34] there was no new data on constant score, so we only analyzed the DASH score. Unlike the previous meta-analyses, [8,10,12] after updating original literature, we found no significant difference in the DASH scores at 1-year after injury between the ORPF group and the non-surgical treatment group. The understanding of PROM (Patient-reported outcome measures) (DASH score) needs to introduce the concepts of smallest detectable change (SDC) and minimal important change (MIC).…”
Section: Discussioncontrasting
confidence: 97%
“…Compared to the study by Woltz et al, [34] there was no new data on constant score, so we only analyzed the DASH score. Unlike the previous meta-analyses, [8,10,12] after updating original literature, we found no significant difference in the DASH scores at 1-year after injury between the ORPF group and the non-surgical treatment group. The understanding of PROM (Patient-reported outcome measures) (DASH score) needs to introduce the concepts of smallest detectable change (SDC) and minimal important change (MIC).…”
Section: Discussioncontrasting
confidence: 97%
“…1,2,10,16 The study by Asadollahi et al, 17 which is in line with the present research, reported a prevalence of male patients when compared to females, and a mean age of 39.1 years. Napora et al 3 and Devji et al 18 reported a mean age between 26.5 and 44.2 years, as well as a higher predominance of men, ranging from 53 to 91% of the study cases.…”
Section: Discussionmentioning
confidence: 74%
“…Beyond these indications, there is controversy over which specific fracture patterns to treat and when. [5][6][7][8] In the UK, clavicle fractures may not be treated by a specialist trauma or upper limb surgeon in the setting of a general fracture clinic. The current literature can be difficult to interpret, leading to potential variation in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these indications, there is controversy over which specific fracture patterns to treat and when. 5 - 8…”
Section: Introductionmentioning
confidence: 99%